Shell Cross‐Linked Micelles as Nanoreactors for Enantioselective Three‐Step Tandem Catalysis. Issue 70 (12th November 2018) - Kuepfert, Michael; Cohen, Aaron E.; Cullen, Olivia; Weck, Marcus
Abstract: Functionalized amphiphilic poly(2‐oxazoline)‐based triblock copolymers that assemble into shell cross‐linked micelles (SCMs) are described. These micelles permit the site isolation of three incompatible catalysts through compartmentalization, thereby enabling three‐step non‐orthogonal tandem processes in one pot. In particular, the acid‐catalyzed ketal hydrolysis to prochiral ketones proceeded in the hydrophilic corona, followed by the Rh‐catalyzed asymmetric transfer hydrogenation to enantio‐enriched alcohols in the cross‐linked shell, and nucleophilic base‐catalyzed acylation in the hydrophobic core. The catalysts are positioned in close proximity on a single micelle support to take advantage of the intramicellar substrate diffusion, yet they are sufficiently spaced apart from each other in physically distinct microenvironments. These compartmentalized micelles are substrate selective and, on a basic level, mimic compartmentalized catalytic architectures found in nature. Abstract : Compartmentalized nanoreactors for non‐orthogonal three‐step tandem transformations are reported. Acid, base, and metal catalysts are spatially isolated on a single poly(2‐oxazoline)‐based micelle support for the hydrolysis of ketals to enantio‐enriched esters in one pot.